Selected Issues of Subsidy for Employment of Persons with Disabilities - Sejkora, Tomáš (PRAWO i WIĘŹ, 2022)
The provision of the subsidy for employment of PWD is one of the tools used by the state to support the employment of disabled persons. However, the design of this subsidy is not optimally set up and only very general legal regulations concerning the process of its provision, including the obligations of the applicant for this subsidy, give a large scope for arbitrary assessment of applications and the creation of administrative behaviour. The administrative behaviour is therefore faced with the need to adjust the granting of this grant from the perspective of a consistent administrative behaviour moving secundum et intra legem. For this reason, the article discusses the answers to specific questions often faced by applicants for this subsidy and identifies the ‘sensitive’ points of current administrative behaviour in the granting of this subsidy.